The Most Appropriate Online Assessment Tools for Language Learning: An Analysis of Their Use and Challenge in EFL Instructions - Hasan, Jhems Richard; Habibie, Alvons (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
The integration of assessment tools with technology can lead to numerous benefits, such as improving the efficiency and practicality of the assessment process and its results. Therefore, this study aimed to map the types of online grading systems in EFL testing classrooms and also determine the challenges faced by users, including EFL lecturers and students. This study involved 10 EFL lecturers and 15 students of the English Education Department of IAIN Sultan Amai Gorontalo, and the instruments used for data collection were observation sheets and a questionnaire. A minimum of 52 online grading systems were accessible through websites and these tools were assessed using instruments produced by the study team to identify any tools that could be employed in the context of language learning, particularly in terms of evaluation. Based on the results, 16 tools were identified for use in the language evaluation process. These included (1) Mentimeter, (2) AnswerGarden, (3) Blooket, (4) Gimkit, (5) Crowdsignal, (6) Google Formulir, (7) Kahoot, (8) Socrative, (9) Quizizz, (10) EdPuzzle, (11) Formative, (12) Floop, (13) JoeZoo, (14) EasyTestMaker, (15) Quia Web, and (16) Edmodo. Furthermore, 5 main components in terms of the challenges faced by EFL lecturers and students in applying these online grading systems in the learning process were identified. These components included preparing to conduct an online assessment, organization of questions, internet connection issues, the use of a device, and controlling a plagiarism/cheating issue.